Immunological Response Of Sheep To Eperythrozoon Ovis Infection - Kanabathy, Shankar Ganesh (2004)

(untitled)
The immunity of sheep to Eperythrozoon ovis (E.ovis) has been investigated through the peripheral blood smears stained with Giemsa. A naturally infected flock monitored for a year revealed the activity of peripheral blood monocytes to be involved in active phagocytosis of infected erythrocytes; a process called erythrophagocytosis. Although neutrophils, lymphocytes and thrombocytes were found to be activated in the initial stage of immune response, the monocytes seemed to predominate the phagocytosis at the later stage of infection during erythrophagocytosis. At all stages and degree of infections, no obvious anaemia, jaundice and emaciation were observed in these well fed sheep flocks. Anaemia was observed in flocks where malnourishment and stress conditions were present with a consistent high degree of parasitaemia. E.ovis infection trial in mice exhibited more lymphocytic activities compared to the sheep , although lymphocytes, neutrophils and thrombocytes were involved in the early enhancement of inflammatory process against E.ovis as per in the sheep. These inflammatory processes were observed at day 20 post infection in mice. Similarly, only monocytes were found to be actively involved in erythrophagocytosis at the later stage of infection prior to the disappearance of the organisms from the peripheral circulation. Increased Kupffer cell activity showed liver was also involved in the removal of infected erythrocytes besides the blood peripheral macrophages. In vitro phagocytosis assay using the Acridine Orange as the flurochrome revealed that peripheral monocytes ingested around eight cells of E.ovis per monocyte within 30 minutes upon contact. These cells were also killed within 30 minutes upon ingestion, characterised as red cells within the cytoplasm of monocytes. The Enzyme–linked Immunosorbent Assay was possible for optimization and was not suitable for further development as the Lang’s method yields impure antigen from blood lysates. Latex test development was hindered due to the various host and immune serum factors that have resulted in non- specific agglutinations. The persistence of infection in the flock throughout the one - year period of observation signified that sheep had been constantly infected with E.ovis and remained carriers for a very long period. The persistent parasitemia may suggest that the immunity to the parasite has been very complex probably due to highly diversed antigenic variants, a characteristic exhibited by most rickettsiae in the Order of Rickettsiales or as a result of detrimental effects of the organism on the immune mechanism. Sheep flocks naturally infected with E.ovis have remained permanent carriers. The findings from this research suggest that the sheep was unable to confer an effective or protective immune response against the pathogen. Peripheral blood macrophages are the most important first line of defense in removing the E.ovis from the peripheral blood.